The Addenbrooke’s Cognitive Examination Revised (ACE-R) and its sub-scores: normative values in an Italian population sample - Siciliano, Mattia; Raimo, Simona; Tufano, Dario; Basile, Giuseppe; Grossi, Dario; Santangelo, Franco; Trojano, Luigi; Santangelo, Gabriella (Neurological sciences, 2016)
The Addenbrooke’s Cognitive Examination Revised (ACE-R) is a rapid screening battery, including five sub-scales to explore different cognitive domains: attention/orientation, memory, fluency, language and visuospatial. ACE-R is considered useful in discriminating cognitively normal subjects from patients with mild dementia. The aim of present study was to provide normative values for ACE-R total score and sub-scale scores in a large sample of Italian healthy subjects. Five hundred twenty-six Italian healthy subjects (282 women and 246 men) of different ages (age range 20–93 years) and educational level (from primary school to university) underwent ACE-R and Montreal Cognitive Assessment (MoCA). Multiple linear regression analysis revealed that age and education significantly influenced performance on ACE-R total score and sub-scale scores. A significant effect of gender was found only in sub-scale attention/orientation. From the derived linear equation, a correction grid for raw scores was built. Inferential cut-offs score were estimated using a non-parametric technique and equivalent scores (ES) were computed. Correlation analysis showed a good significant correlation between ACE-R adjusted scores with MoCA adjusted scores ( r = 0.612, p < 0.001). The present study provided normative data for the ACE-R in an Italian population useful for both clinical and research purposes.